THE STATE – AS A PARTICIPANT IN CIVIL-LEGAL RELATIONS - Nadirbekova Umida Karamatdin qizi (Scholar Express Journal, 2022)
This article discusses civil-legal relations and their features, their content and state participation in relations.
Keywords: Civil-legal relations; participants in civil-legal relations; the state as a participant